Le dictionnaire de chimie en lingÃ¡la pour les élÃ¨ves de Kinshasa - Sene Mongaba, Bienvenu (Lexikos, 2013)
Dictionary of Chemistry in LingÃ¡la for Kinshasa Students. In well-documented languages, the lexicographer aiming to make a specialized dictionary will process an available corpus to extract data (candidate terms, definitions and examples). This approach is not suitable for poorly documented languages, for which texts in any given specialized domain may be few and far between. This is the case with LingÃ¡la, spoken in the city of Kinshasa, in the field of chemistry. Besides processing the available corpora, the lexicographer needs to coin terms for concepts and to create definitions and examples in order to produce dictionaries meeting users’ expectations. For this purpose, one of the two following methodologies can be adopted. The first, and more commonly employed methodology adopts the translation approach. A corpus which is available in the source language is processed to extract lemmas, definitions and examples and eventually classify data in the source language. The document obtained in this way is then translated into the target language. According to the second methodology, in the absence of well-documented specialized corpora in the target language, concepts are defined and coined directly in the target language. Examples are also produced directly in the target language. This approach calls for the lexicographer to be an expert in the given field or for him/her to work with an expert who can produce specialized knowledge in the target language. Then the lexicographer will submit his/her findings to other native speakers, who are also experts in that given field for validation. This is the methodology we have adopted and we are to describe in this paper. In fact, this article describes the approach we have followed in order to make a LingÃ¡la–French bilingual dictionary of chemistry for students and teachers of the third year of secondary school in Kinshasa.